PFOS-elicited metabolic perturbation in liver and fatty acid metabolites in testis of adult mice - Lee, Wang Ka; Lam, Thomas Ka Yam; Tang, Hiu Ching; Ho, Tsz Chun; Wan, Hin Ting; Wong, Chris Kong Chu (Frontiers in Endocrinology, 2023)
Introduction Multiple factors can contribute to sub-fecundity, including genetics, lifestyle, and environmental contaminants. PFASs are characterized as “forever chemicals” due to their ubiquitous contamination and their persistence in the environment, wildlife, and humans. Numerous studies have demonstrated that PFAS exposure adversely affects multiple bodily functions, including liver metabolism and gonadal function. It is unclear, however, how the disruption of hepatic fatty acid metabolism affects testicular function. Methods In this study, male mice were administered 0.3 and 3 μg/g body weight of PFOS for 21 days. Results Our data showed that PFOS exposure caused hepatic steatosis, as evidenced by significant increases in triglyceride levels, expression of ATP-citrate lyase, and fatty acid synthase, as well as fasting insulin levels. PFOS perturbed the expression levels of hepatokines, of which fibroblast growth factor-21 (Fgf-21), leukocyte cell-derived chemotaxin-2 (Lect-2), and retinol-binding protein-4 (Rbp-4) were significantly reduced, whereas angiopoietin-like 4 (Angptl4) was noticeably increased. While Rbp-4 and Fgf-21 are known to contribute to spermatogenesis and testosterone synthesis. In PFOS-exposed groups, testicular ATP, and testosterone decreased significantly with a significant increase in the expression of peroxisome proliferator-activated receptor-coactivator 1α. Mass spectrophotometry imaging revealed the localization of PFOS in testes, along with significant increases in fatty acid metabolites. These included arachidonic acid, dihomo-α-linolenic acid, dihomo-γ-linolenic acid, oxidized ceramide, diacylglycerol, phosphatidylcholine, and phosphatidylethanolamine, which are associated with inflammation and post-testicular causes of infertility. Discussion This study revealed potential links between PFOS-elicited changes in hepatic metabolism and their impacts on testicular biology. This study provides insights into alternative targets elicited by PFOS that can be used to develop diagnostic and therapeutic strategies for improving testicular dysfunction.